Oscilations & waves - Flash Multimedia (United Kingdom : Fable Multimedia, 1998)
This CD-ROM has fifteen highly interactive teaching tools to adress abstract concepts such as how a longitudinal wave moves and how an interference pattern is formed
Keywords: Plasma waves -- study and teaching; Oscillations -- Study and teaching; Physics